2009
DOI: 10.1063/1.3073006
|View full text |Cite
|
Sign up to set email alerts
|

Computational confirmation of an abnormal Mach reflection wave configuration

Abstract: For the Mach reflection ͑MR͒ of symmetric shock waves of opposite families, only the wave configuration of an overall Mach reflection ͑oMR͒ consisting of two direct Mach reflections ͑DiMR+ DiMR͒ is theoretically admissible. For asymmetric shock waves, an oMR composed of a DiMR and an inverse Mach reflection ͑InMR͒ is possible if the two slip layers assemble a converging-diverging stream tube, while an oMR including two inverse Mach reflections ͑InMR + InMR͒ is absolutely impossible. In this paper, an overall M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The primary principle of the scheme aims at removing non-physical oscillation across strong discontinuities by making use of the dispersion characteristics of the modified equation instead of adding artificial viscosity. The DCD scheme has also been applied successfully to chemically reacting flows for compressible multi-component mixtures [24] and flows with strong shock wave interactions [25,26]. Such mentioned applications have shown that the DCD scheme is fairly robust, computationally efficient, and capable of resolving strong discontinuities.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The primary principle of the scheme aims at removing non-physical oscillation across strong discontinuities by making use of the dispersion characteristics of the modified equation instead of adding artificial viscosity. The DCD scheme has also been applied successfully to chemically reacting flows for compressible multi-component mixtures [24] and flows with strong shock wave interactions [25,26]. Such mentioned applications have shown that the DCD scheme is fairly robust, computationally efficient, and capable of resolving strong discontinuities.…”
Section: Introductionmentioning
confidence: 94%
“…In the original DCD scheme [22,23], the Steger-Warming (SW) method was suggested to obtain the split fluxes e F AE or e G AE . For the gasdynamic flows with an ideal gas EOS, the method works well and very efficiently [24][25][26]. Based on the Steger-Warming method, the split flux for the flux vector, e F ¼ n x F þ n y G, in the computational space can be written as…”
Section: Modification Of Dcd Scheme For Flow Supercavitationmentioning
confidence: 99%
“…1 (right). The DCD scheme has been applied to simulate shock wave problems in inert or reacting flows [21][22][23][24][25][26][27]. However, serious spurious oscillation occurs when the original DCD scheme is used for the simulation of hypervelocity test flow in the detonation-driven expansion tube, JF-16 [13,14].…”
Section: The Original Dcd Scheme For Multi-component Systemmentioning
confidence: 99%
“…The DCD scheme, without any tunable parameters, avoids encountering the 'carbuncle' phenomena altogether even for the case of very strong shock wave. It has also been successfully applied to chemically reacting flows for compressible multi-component mixtures [21][22][23][24][25] and flows in the presence of strong shock wave interaction [26,27]. The mentioned applications have attested to the DCD scheme as fairly robust, computationally efficient, and capable of resolving strong discontinuities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation